Pengaruh Komunikasi Pembelajaran Online Terhadap Kualitas Belajar Siswa Di MAN 3 Bone Pada Masa Pandemi Covid-19 - Pusvita , Arwini; Zelfia, Zelfia; Rahmawati , Sitti (UNIVERSITAS MUSLIM INDONESIA, 2022)
ARWINI PUSVITA. 2022. The Effect of Online Learning Communication on the Quality of Student Learning at MAN 3 Bone During the Covid-19 Pandemic (supervised by Andi Muttaqim Mustari and Sitti Rahmawati) Communication Studies Thesis, Faculty of Letters, Indonesian Muslim University.The purpose of the study was to determine the effect of online learning communication on the learning quality of students in class X IPA 4 and X IPA 5 at MAN 3 Bone. Bones. The method used in this research is descriptive statistical analysis quantitative method with the data collection process using a survey in the form of a questionnaire, and data analysis using multiple linear regression analysis. This thesis discusses online learning communication on the quality of learning for students in class X IPA 4 and X IPA 5 at MAN 3 Bone. Due to the COVID-19 pandemic, the MAN 3 Bone school forced online learning, so that it affected the communication between students and teachers. Good communication in the learning process is needed to maintain the quality of student learning.The results of the study using the t test with the results of the t value = 18,716 greater than t table = 1,990 (18,716 > 1,990) then there is an effect. And if it is seen from the significance value = 0.000 which is smaller than 0.05 (0.000 < 0.05), then there is also the influence of online learning communication on the learning quality of students in class X IPA 4 and X IPA 5 at MAN 3 Bone. The indicators that influence online learning communication on the quality of learning for students in class X IPA 4 and X IPA 5 at MAN 3 Bone are the characteristics of students in learning materials, learning media, learning facilities, learning environment, internet network factors, higher laziness. The theory used in this research is S-O-R (Stimulus-Organism-Response) theory and behavioristic learning theory.